The Efl Teachers’ Teaching Methods At SMPIT Tunas Cendekia Mataram - Imansyah, Imansyah (Jurnal Ilmiah Mandala Education (JIME), 2021)
This descriptive qualitative research was aimed at finding out the methods employed by the EFL Teacher at SMPIT Tunas Cendekia Mataram. The setting of the research was in SMPIT Tunas Cendekia Mataram. The subject of this research was the 7th grade EFL teacher consisting of one single teacher. This research was designed as a descriptive qualitative research. The data were collected through, interview and document study (lesson plan). Data was analyzed by using the theories proposed by Larsen-Freeman (1986) and Richards and Rodgers (2001) classification. In relation to problem raised, the study identifed that there were three methods the teacher employed in the teaching process. They were Community Language Learning, Direct Method, and Audio-Lingual Method. Community Language Learning was employed five (5) times for five (5) different meetings, Direct Method was employed two (2) times for two different meetings, and Audio-Lingual Method was employed one (1) time.